(untitled) (Scientiae Studia, 2012)
The aim of this article is to address the question of the ontology of quantum chemistry. To this end we will focus on the concept of chemical bond, from the perspective of the two approaches by means of which the Schrödinger equation is applied to molecular chemical systems: the Theory of Valence Bond (VB) and the Theory of Molecular Orbital (MO). On the basis of the presentation and the comparison of these two approaches, we will conclude that, in spite of their traditional names, strictly speaking they should be considered, not theories, but models; in particular, models that include concepts and laws coming both from quantum mechanics and from structural chemistry. These conclusions will allow us to argue that quantum chemistry does not have an autonomous ontological referent, but it is a scientific domain whose validity rests on its practical success in computation and prediction. Finally, we will show that the approaches VB and MO open a new perspective with respect to the concept of model in empirical sciences.